2006
DOI: 10.1118/1.2219774
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of a Cyberknife stereotactic radiosurgery system

Abstract: This study investigated small-field dosimetry for a Cyberknife stereotactic radiosurgery system using Monte Carlo simulations. The EGSnrc/BEAMnrc Monte Carlo code was used to simulate the Cyberknife treatment head, and the DOSXYZnrc code was implemented to calculate central axis depth-dose curves, off-axis dose profiles, and relative output factors for various circular collimator sizes of 5 to 60 mm. Water-to-air stopping power ratios necessary for clinical reference dosimetry of the Cyberknife system were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 14 publications
10
70
0
Order By: Relevance
“…In particular, for the diode 6 found s c,p = 0.719± 0.015, compared to 0.710 of the present study; for the 7.5 mm collimator they reported s c,p = 0.849± 0.012 and for the 10 mm collimator s c,p = 0.892± 0.011, compared to 0.852 and 0.895 of the present study, respectively. Araki et al 5 reported a graphical representation of average s c,p values from 14 Cyberknife units installed in Japan, giving s c,p = 0.72 for a diode detector and the 5 mm collimator, 0.845 for the 7.5 mm, and 0.885 for the 10 mm collimator. The diode detector employed in those studies was not of the same type reported in this work, however, its characteristics could be considered similar; both detectors were an unshieldedtype diode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for the diode 6 found s c,p = 0.719± 0.015, compared to 0.710 of the present study; for the 7.5 mm collimator they reported s c,p = 0.849± 0.012 and for the 10 mm collimator s c,p = 0.892± 0.011, compared to 0.852 and 0.895 of the present study, respectively. Araki et al 5 reported a graphical representation of average s c,p values from 14 Cyberknife units installed in Japan, giving s c,p = 0.72 for a diode detector and the 5 mm collimator, 0.845 for the 7.5 mm, and 0.885 for the 10 mm collimator. The diode detector employed in those studies was not of the same type reported in this work, however, its characteristics could be considered similar; both detectors were an unshieldedtype diode.…”
Section: Discussionmentioning
confidence: 99%
“…2 Discrepancies in total scatter factor values have been reported for the smallest collimators of the Cyberknife radiosurgery system. [3][4][5][6][7][8][9] Such discrepancies might be explained as a contribution of several factors: differences in the choice of the dosimeters among centers, possible inaccuracies in the experimental setup ͑in particular for the 5 mm cone͒, and differences in beam parameters between units ͑in particular the electron beam width͒. In fact, it has been observed for other linear accelerators 10 that units with a similar design can have spot sizes that can differ up to 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…One useful tool in dealing with small field effect is Monte Carlo (MC) simulation. Many recent studies have applied Monte Carlo simulations to examine the output factors of small field sizes used for radiosurgery such as CyberKnife, 6 , 7 Gamma Knife, 8 , 9 and Brainlab (10) . In addition, numerous studies have used Monte Carlo simulation to examine the accuracy of diode detectors measurements for small field dosimetry 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the MC‐based linac head is verified using PDDs and beam profiles for several rectangular fields formed by specifically shaped collimators or variable jaws 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 . On the other hand, the secondary collimator in the Vero4DRT is of a fixed type and the field is formed using the MLC only.…”
Section: Methodsmentioning
confidence: 99%
“…First, the linac head, exclusive of MLC, is modeled against measurement data as a patient‐independent component. Next, the patient‐dependent MLC model is compared with several measurement data using well‐commissioned phase space data (PSD) from the linac head 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 …”
Section: Introductionmentioning
confidence: 99%